2004
DOI: 10.1097/00001665-200403000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Crouzon Syndrome: Phenotypic Signs and Symptoms of the Postnatally Expressed Subtype

Abstract: In a retrospective study, the characteristics of a group of patients (n = 9) with a postnatally expressed Crouzon syndrome were described. Although they do not always display the physical signs of craniosynostosis, such patients are highly at risk of developing symptoms secondary to multiple suture synostosis. By reviewing the hospital files, radiographs, and three-dimensional computed tomography scans of these patients, it was possible to describe the pattern of suture obliteration chronologically. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
3
22
1
1
Order By: Relevance
“…22,23 In addition, animal studies have revealed that FGFR2 is expressed at the neural tube and cranial base during embryogenesis. [24][25][26][27] Several studies reported abnormalities of the skull 2,5,9,28,29 and skull base 9,13,30 in Crouzon syndrome in humans and in mice. [31][32][33] Thus, it is likely that FGFR2 gene mutations have an effect on hindbrain development and give rise to abnormal growth of its surrounding bone plates (i.e., the foramen magnum).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, animal studies have revealed that FGFR2 is expressed at the neural tube and cranial base during embryogenesis. [24][25][26][27] Several studies reported abnormalities of the skull 2,5,9,28,29 and skull base 9,13,30 in Crouzon syndrome in humans and in mice. [31][32][33] Thus, it is likely that FGFR2 gene mutations have an effect on hindbrain development and give rise to abnormal growth of its surrounding bone plates (i.e., the foramen magnum).…”
Section: Discussionmentioning
confidence: 99%
“…Although bicoronal synostosis is most common, Crouzon syndrome can present with late-onset pansynostosis. 18,19 It is important to be aware of this possibility in a child with a crouzonoid appearance, because apparently mild distortion of the skull shape may mask the presence of raised ICP. The association of crouzonoid facies with acanthosis nigricans is caused by a specific FGFR3 mutation (see below).…”
Section: Molecular and Genetic Basis Of Diseasementioning
confidence: 99%
“…2 Hoefkens and coworkers documented PPP in 9 of 73 patients with Crouzon syndrome. 7 Affected patients had absent or mild clinical features, such as exorbitism and midfacial retrusion, in early infancy that appeared to progress with the onset of craniosynostosis. The authors referred to these patients as a "postnatally expressed subtype" of Crouzon, a finding reportedly discussed by Dr. Tessier.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike more common forms of craniosynostosis, this entity typically manifests as a normally proportioned, albeit smaller than average, head shape. 2,7,10,11 The muted effect on calvarial form is attributable to the latent timing of sutural closure, usually occurring in the first 2 years of life. The majority of patients have an associated syndrome-Crouzon syndrome being most common 2,11 -but the characteristic craniofacial features can be subtle and easily overlooked.…”
mentioning
confidence: 99%